2021
DOI: 10.1038/s42005-021-00623-2
|View full text |Cite
|
Sign up to set email alerts
|

Tunable polarization-induced Fano resonances in stacked wire-grid metasurfaces

Abstract: Stacked metasurfaces are being investigated in light of exploring exotic optical effects that cannot be achieved with single-layered metasurfaces. In this article, we theoretically demonstrate that metallic wire-grid metasurfaces with specific polarization properties have the ability to induce tunable Fano resonances when they are stacked. The developed original model—combining a circulating field approach together with an extended Jones formalism—reveals the underlying principle that gives rise to the polariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…They are well established in the literature [15][16][17][18][19][20][21][22], first described by Fano as a means to explain the asymmetric spectra from helium atoms subjected to inelastic scattering from electrons [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are well established in the literature [15][16][17][18][19][20][21][22], first described by Fano as a means to explain the asymmetric spectra from helium atoms subjected to inelastic scattering from electrons [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature Fano resonances have been found for a multitude of different structures, or metamaterials (MMs) [21]. The complexity in the designs of the MMs ranges from one-dimensional gratings and structures such as split-ring resonators, to more intricate threedimensional structures [12,14,16,17,19,20,22]. Furthermore, the Fano resonances of the MMs have in different studies been shown to be highly tunable, hence enabling the possibility to tailor the MMs depending on the task [14,17,[19][20][21]25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation